Ovarian Fibroma with Substantial Calcification: An Uncommon Case Presentation - Chendong He; Wei Yang (Caucasian Medical Journal)
Ovarian fibroma is a rare benign tumor of the ovary that is composed of fusiform fibrous cell components. Ovarian fibroma can occur at any age, and it is more common in postmenopausal or postmenopausal women. The clinical manifestations of ovarian fibroma are not typical; they are usually characterized by no obvious symptoms and mostly accidental imaging findings. The density and signal of ovarian fibroma are generally uniform, and necrosis, cystic degeneration, and calcification are rare. We report a 25-year-old young woman who accidentally discovered a large calcified mass on the right side of the pelvic cavity during a computed tomography examination of the lumbar spine. The mass was pathologically confirmed as calcified ovarian fibroma.